The Credit Spread and U.S. Business Cycles - Junsang Lee; Keisuke Otsu (University of Kent, School of Economics, 2011)
In this paper, we construct a dynamic stochastic general equilibrium model in order to investigate the impact of credit spread shocks on the U.S. business cycle. We find that the shocks to the investment specific technology and the preference weights on consumption and leisure are the main sources of output fluctuation. Shocks to the credit spread and productivity are the main source of the fluctuation in the investment to output ratio. Credit spread shocks also had a significant impact on the output during the recent financial crisis.
Keywords: E13; E32; 330; Credit Spread; Business Cycles; Investment Specific Technology